Lateral Harvest of an Osseous-Based Quadriceps Tendon Autograft Results in Thinner Remaining Patellar Bone. Issue 5 (6th May 2022) - Perry, Allison K.; Dandu, Navya; Knapik, Derrick M.; Inoue, Nozomu; Gursoy, Safa; Bush-Joseph, Charles A.; Yanke, Adam B.; Chahla, Jorge
Background: Patellar fracture after quadriceps tendon (QT) autograft harvest for anterior cruciate ligament reconstruction (ACLR) has been reported in up to 8.8% of patients. Purpose: To determine the thickness of the remaining patellar bone across the QT graft harvest location while providing clinical guidance for safely harvesting a patellar bone block when using a QT graft in ACLR. Study Design: Descriptive laboratory study. Methods: Medial and lateral QT graft boundaries were marked using a bone saw on 13 cadaveric patellae, and 3-dimensional computed tomography models were created. After the harvest of a virtual bone block with a maximum depth of 10 mm, the thickness of the remaining bone was measured across the graft harvest location in 9 zones. The thickness of the remaining bone was analyzed according to zone, graft harvest location, and patellar facet length. Risk zones were defined as <50% total patellar depth remaining. Results: We observed substantial variability in QT bone block harvest location, in which the distance between the lateral boundary of the harvest location and the lateral patellar cortex was from 21.2% to 49.2% of the axial patellar width. There was significantly less bone remaining in the lateral columns (mean ± SD, 7.56 ± 2.19 mm) compared with the medial columns (9.83 ± 2.10 mm) of the graft harvest location ( P = .028). The number of risk zones was significantly associated with distance to the lateral cortical edge, with an increase in 0.59 zones with every 1-mm decrease in distance to the lateral cortex edge ( b = -0.585; R 2 = 0.620; P = .001). With every 1-mm increase in the distance of the lateral cortex to the lateral graft boundary, the thickness of bone remaining in the lateral column increased by 0.412 mm ( P < .001). No risk zones were encountered when the lateral boundary of the harvest location was created 18.9 mm from the lateral edge of the patella or 43% of the total patellar width from the lateral edge. Conclusion: Harvest of a more laterally based QT autograft bone block resulted in thinner remaining patellar thickness, increasing the potential of encountering a risk zone for fracture. Clinical Relevance: Care should be taken to avoid harvesting the patellar bone block too laterally during ACLR.